Spatio-Temporal Distribution of Phytoplankton and Water Quality of Some Rivers of Haute Sanaga Department (Central Africa) - Pascale, Banga Medjo; Félix, Bilong Bilong Charles; Hubert, Zébazé Togouet Serge (Journal of Biology and Life Science, 2023)
In Cameroon, rivers are subjected to physicochemical disturbances, which increase the degradation of water quality. The aim of this study was to determine the spatio-temporal diversity of the phytoplankton groups and to evaluate the environmental parameters of the sampling sites in order to assess the quality of water in two hydrographic networks. Physicochemicals analyzes were carried out according to the standard methods while phytoplankton organisms were harvested by direct sampling and analyzed by the Utermöhl method. The analysis of Ammonia Nitrogen, Dissolved Oxygen, Electric Conductivity, Nitrates, Orthophosphates, pH, Temperature, and Turbidity.of water revealed the poor state of health of the water. Data from the Long Dry Season differed significantly (p < 0.05) from those recorded in other seasons. The phytoplankton communities were made up of Chlorophyta, Chrysophyta, Cyanophyta, and Euglenophyta with 11 classes dominated by Bacilliarophyceae (12 210 Ind/mL) and Cyanophyceae (6 208 Ind/mL). Phytoplankton densities were higher the Long Rainy Season and much lower in the Small Dry Season than in the Long Dry Season. Station near NODISCAM indicated significant organic pollution under the effect of agro-industrial discharges operating upstream of this company. For this station, the different values showed significant differences (p < 0.05) from one station to another. Finally, spatio-seasonal variations of phytoplankton densities showed logical responses to changes of physicochemical conditions in the environment. This work highlights the need to treat wastewater from collection channels before its dump into the natural environment, to prevent progressive eutrophication of the receiving aquatic environment, and poisoning by water consumption.